How Does Brand Experience Affect Brand Loyalty Through a Brand Satisfaction? - Rahmasadia, Annisa Meira; Taufiq Ismail (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this research is to identify the effects of brand experience on the loyalty of Starbucks’ customers in Malang City to the brand with brand satisfaction as the mediating variable. Competition in coffee shop industry in the city has made companies in this sector feel the need of improving the brand loyalty of their customers in order to survive the competition. The population of this quantitative research is all customers of Starbucks in Malang City, from which 250 people with the minimum age of seventeen years and have made at least two transactions were selected as the sample. The data was analyzed using PLS-SEM (Partial Least Squares – Structural Equation Modeling) after passing the outer and inner model coefficient test and bootstrapping. This stud finds that brand experience positively influences brand satisfaction, that brand experience and brand satisfaction positively influence brand loyalty, and that brand experience affects brand loyalty through the mediation of brand satisfaction. Therefore, if brand experience and brand satisfaction increase, it will be followed by enhancements in the brand loyalty of Starbucks’ customers in Malang City.